RESEARCH ON RELIABILITY OF LONGITUDINAL ROADHEADER’S ROTARY TABLE BY ADAMS - ZHAO LiJuan; ZHU Shuai; LIU XuNan (Jixie qiangdu)
Rotary table is an important part of roadheader,it bears complex and changeable loads,so it is the key component of roadheader’s design. When the cutting head horizontal swing,the superposition between cutting resistance and cutting unit gravity is an important reason which caused the fracture of rotary table. Based on the theory of rock breaking of cutting head,found the optimal performance design parameters and simulated the load spectra of roadheader by using the roadheader’s aided design and load calculation software of cutting head. The rigid-flex coupled model of roadheader has been established and the weak areas of the rotary table has been found by dynamic simulation,then optimizing the structure of the rotary table,the force of the optimized rotary table is uniform,and it can work reliably and meet the requirements.